Pemodelan dan Simulasi VANETs Menggunakan Federated Mobility Model; Sebuah Artikel Tinjauan - Afdhal Afdhal (Universitas Syiah Kuala, 2014)
The emergence of Vehicular Ad-hoc Networks (VANETs) as part of the Intelligent Transportation Systems (ITS) technology development was expected to become an advanced method to solve the transportation system problem. The implementation of VANETs is expected to provide a new solution for traffic management strategy. Its main targets is to continue prioritizing traffic safety and to prevent the accidents on the roads. One of the VANETs problems before being implemented in the real world is the degree of freedom of the vehicle's mobility that limited by the road topologies. Various modellings and simulations have been performed to produce the most realistic mobility model. However, those models had become new paradigms due to various factors that limited them. The presence of the federated mobility model as an approach for traffic mobility modeling is considered to be able to provide more realistic and accurate VANETs simulation. Therefore, this article presents some brief reviews and contrast a number of the simulation and mobility models that have been used widely as compared to the federated mobility models that have developed until the present. The article's objective is to facilitate a better understanding of the traffic mobility modeling for the VANETs simulation that started from the interaction process until the integration between simulators. The understanding of the traffic mobility models will complement the knowledge that enable to perform the simulation of the VANETs implementation approaching the real conditions.